2022
DOI: 10.15388/stepp.2022.34
|View full text |Cite
|
Sign up to set email alerts
|

“It was a Shock to the Whole Family”: Challenges of Ukrainian Families Raising a Child with Autism

Abstract: Based on the family-centered approach and a consumer perspective this research examines the overall level of satisfaction with educational and social services of the families raising children with autism or autism spectrum disorders (ASD) in Lviv (Ukraine) and the challenges in interactions of such families with services. The survey (90 parents who are social work clients) and individual semi-structured interviews (30 parents) were used. The findings indicate the respondents’ evaluation of the services t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A pre-intervention survey found that families raising children with autism experience difficulties in all areas of family functional ability (Semigina & Stoliaryk, 2022).…”
Section: Findings From the Pre-intervention Surveymentioning
confidence: 99%
“…A pre-intervention survey found that families raising children with autism experience difficulties in all areas of family functional ability (Semigina & Stoliaryk, 2022).…”
Section: Findings From the Pre-intervention Surveymentioning
confidence: 99%